Evaluation of basketball set offense based on duration and major tactical elements - Selmanovic, A.; Milovukovic, S.; Bujan, T. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
The study analyzed the influence of duration and quantity of major tactical elements on 1337 set offense outcome taken from Euroleague playoff games of the 2021/22 season. Using Spearman's rank correlation and logistic regression analysis, the variables used in the study formed a principal component defined as Tactical offensive duration. Contrary to expectation, this component did not show to be an indicator sensitive enough to differentiate successful from unsuccessful set offenses (p<.05), proving that both outcomes contain practically the same frequency of passes (x = 3,3), major tactical elements (x = 4,6), as well as equal time of realization (x = 16 s). The authors suggest slight enhancement of measuring instrument. The findings help coaches to shift focus towards the nature of tactical tasks in elite basketball and the quality of individual and group performance independently from the offensive duration in order to optimize their strategies for future competition.